RETRACTED: Modeling COVID-19 Impact on Consumption and Mobility in Europe: A Legacy Toward Sustainable Business Performance - Ameer, Waqar; Chau, Ka Yin; Mumtaz, Nosheen; Irfan, Muhammad; Mumtaz, Ayesha (Frontiers in Psychology, 2022)
This paper has explored the impact of COVID-19 Induced Decline in Consumer Durables and Mobility on NO2 Emission in Europe by providing empirical and graphical justifications based on CPI and GDP Deflator indexes. The empirical estimations show that CO2 and NOx emission along with other greenhouse gasses drastically decreased in the wake of COVID-19 induced lockdowns and decrease in the demand of consumer goods in Europe. This means that COVID-19 improved environment in the European Region. However, high cost (e.g. unemployment, loss of life and social segregation) makes COVID-19 an unstable solution to environmental woes where positive impact of COVID-19 on environment achieved in short run cannot be guaranteed in the long run. Beside environment, COVID-19 drastically curtailed economic activities and exposed them to the risk of economic crisis particularly in case of Europe.